Analisis Dampak Pembiasaan Berdoa Bersama terhadap Peningkatan Kedisiplinan Siswa di Kelas III SD Negri 2 Bakan - Erna Sudariah (Journal of Elementary Education Research, 2025)
This study aims to analyze the impact of the routine practice of communal prayer on improving student discipline in the third grade at SD Negeri 2 Bakan. The research employs a qualitative descriptive approach with a case study methodology. Data was collected through a systematic search and analysis of academic documents, including scientific journals, books, and conference proceedings from databases like Google Scholar, focusing on keywords such as "student discipline," "character education," and "prayer in schools." The data analysis technique used was thematic content analysis, which was employed to identify recurring patterns, theoretical frameworks, and key findings related to the link between spiritual routines and behavioral discipline. The main findings indicate that the habit of praying together has a significant positive impact on student discipline. This is manifested in behavioral changes such as improved punctuality, better concentration during lessons, and an increased sense of responsibility. This practice fosters a calmer and more orderly classroom environment, serving as an effective transition from informal to formal learning. In conclusion, this study highlights that regular spiritual activities, such as communal prayer, can be a powerful and effective instrument for character development, particularly in cultivating discipline among elementary school students.